Pesticide residues in vegetables produced in rural south-western Uganda - Hannington, Ngabirano; Grace, Birungi (Elsevier, 2022)
This study investigated seven pesticides in vegetables produced in rural South-western Uganda to determine their suitability for human consumption. Pesticide residue concentrations (ppm) were determined using QuEChERS method, LC–MS/MS, GC–MS/MS and UV–Vis. Cypermethrin, dimethoate, metalaxyl, profenofos, malathion, dichlorvos and mancozeb concentrations detected in sprayed samples ranged between 0.00403 and 0.05350, 0.17478–62.60874, 0.12890–3.55681, 0.00107–0.59722, 0.03144–0.63328, 0.00240–0.34102 and 0.00001–0.00244, respectively. The residues exceeded MRLs in sprayed samples (59.52%), unsprayed samples (18%) and market samples (8%). The quality index of the market vegetables was found to be optimal (14.29%), good (75%), adequate (3.57%) and inadequate (14.29%). Pesticide residues may lower food quality and pose risk to human health. Therefore, regulation and monitoring pesticide residues in vegetables produced in southwestern Uganda in order to avoid harmful effects on human health would be paramount.